Simple and complicated rectal diverticula: endoscopic analysis of a case series from Brazil - Motta,Guilherme Lang (2012)
INTRODUCTION: Diverticular disease of the colon is a very common condition, present in most of the elderly population. However, the occurrence of rectal diverticula is extremely unusual. It is typically an incidental finding at colonoscopy. OBJECTIVE: Describe epidemiological, clinical, surgical and endoscopic characteristics of a case series of rectal diverticula in Brazil. METHODS: Four patients with rectal diverticula were analyzed in terms of symptomatology, associated conditions and colonoscopy findings. Endoscopic findings were discussed individually. RESULTS: The prevalence of rectal diverticula at our endoscopy unit was 0.15% of all colonoscopies, affecting 0.74% of patients with colonic diverticulosis. The endoscopic analysis showed the diverticulum ostium with mean size of 2.3 cm, depth of 2.8 cm and anal margin distance of 6.8 cm. Colonoscopy also demonstrated simple rectal diverticulum in all patients. Diverticula were located in the anterior, right lateral and posterior walls of the rectum. One patient developed diverticulitis as complication and underwent to diverticulectomy. CONCLUSIONS: Rectal diverticulum is an incidental finding at colonoscopy and associated with diverticulosis. Its rarity and specific colonoscopic characteristics make it a unique entity. Asymptomatic in most cases, it rarely needs intervention. Surgery is reserved for complicated cases.